Future-time framing: The effect of language on corporate future orientation - LIANG, Hao (Institutional Knowledge at Singapore Management University, 2018)
We examine how international variation in corporate future-oriented behavior, such as corporate social responsibility and research and development investment, could partially stem from characteristics of the languages spoken at firms. We develop a future-time framing perspective rooted in the literatures on organizational categorization and framing. Our theory and hypotheses focus on how companies with working languages that obligatorily separate the future tense and the present tense engage less in future-oriented behaviors, and this effect is attenuated by exposure to multilingual environments. The results based on a large global sample of firms from 39 countries support our theory, highlighting the importance of language in affecting organizational behavior around the world.